Garden of the mind - Wang, Yaw-Jun, author; Voss, Gary Wayne, advisor; Lundberg, Thomas R., committee member; Frickman, Linda, committee member; Bowman, James P., committee member (Colorado State University. Libraries, 1998)
Life is an ongoing process. My philosophy of life is based on a feeling of temporary presence. I don't seek immortality; instead, I desire a life of rural simplicity. For the past three years, I have experienced the unique life situation of living far away from my motherland of Taiwan. Exploring the American continent and recalling my past memories and experiences have formed the reality of my existence here. I am interested in presenting feelings and thoughts in a metaphorical way. Garden of the Mind, a metaphorical environment, is filled with carefully composed objects. The idea of creating these objects comes from the emotional aspects of my life experiences, such as my hopes and fears. In this garden, nothing is perfect. Objects here were created and arranged to reveal the reality of my life experiences as a whole. In order to convey the concept of modifying natural resources into cultural objects, I combined organic and human-made materials. Branch and root came from the physical context of nature, and were engaged with human-made objects such as light bulb, cardboard, and cloth. The choice of materials allows me to examine how I feel about the surroundings. For example, I use cardboard as a medium to express a feeling of temporary presence. On the other hand, the choice of colors represents my awareness of some specific colors. For instance, I use blue in my light bulb piece, Blue, to convey my perception of the universe. As a result, the ongoing process of life's struggles and changes allows me to examine myself. The choice of life's struggles and changes, and the choice of materials and colors have become the most important aspects of my creation. To keep an eye on the wonders of life, I don't seek immortality but a life of rural simplicity.
Keywords: mixed media; Sculpture; Installations (Art)